Perlindungan Hukum Terhadap Profesi Advokat dalam Pencucian Uang - Putu Bagus Dananjaya (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
Money laundering is a special class of crimes and is classified as a major crime regulated in Law Number 8 of 2010 concerning the Prevention and Eradication of Anti-Trafficking Drugs. Has the potential to damage economic, security, and social consequences. The strategy to eradicate money laundering requires the advocate profession to participate in efforts to eradicate money laundering as stipulated in Government Regulation Number 43 of 2015. The birth of this Government Regulation poses obstacles for professionals. In this Government Regulation one of them is the advocate profession which is classified as a reporting party who is obliged to submit suspicious financial transaction reports to PPATK. On the one hand, Article 19 paragraph (1) of the Advocate Law also states that an advocate is obliged to keep everything secret obtained from his client because of his professional relationship, unless specified by law. In writing this study, a type of normative juridical study is used with a conceptual approach also a legislative approach. The regulation regulated in Government Regulation No. 43 of 2015 is because the advocate profession is vulnerable to being used by money laundering perpetrators. With the obligation, it will circumstantial avoid them from using advocates with their immunity rights to do the crimes.